Acercamiento al problema social de la pobreza de las nociones de pobreza y los mecanismos causales (2009)
ABSTRACT: To speak of the social problem of the poverty requires to concatenate subjects such as the causes, conditions that facilitate the phenomenon, the consequences and the possible solutions, nevertheless, when centering the attention in the poverty, glimpse problems such as: the lack of consensus about its definition, it's more important dimensions and the actions to undertake to diminish it and to finish it. The central thesis is that it is possible to associate the theory of the capacities and the causal mechanisms of the poverty and this would allow a better approach to this phenomenon. One of the conclusions is that it is possible to study the poverty of capacities by means of causal mechanisms and although it moves away of the obtaining of comparative indices, approaches with more clarity the compression of the social problem.